2016
DOI: 10.3389/fpsyg.2016.01675
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Frequency of Inner Speech: Differential Relations with Cognitive and Non-cognitive Factors

Abstract: Inner speech plays a crucial role in behavioral regulation and the use of inner speech is very common among adults. However, less is known about individual differences in the frequency of inner speech use and about the underlying processes that may explain why people exhibit individual differences in the frequency of inner speech use. This study was conducted to investigate how individual differences in the frequency of inner speech use are related to cognitive and non-cognitive factors. Four functions of inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 47 publications
3
20
0
3
Order By: Relevance
“…There are additional studies that are pertinent to the cognitive disruption hypothesis. Using a Chinese college student sample, Ren et al. (2016) found significant relationships between impulsivity and self-talk frequency.…”
Section: The Cognitive Disruption Hypothesismentioning
confidence: 91%
See 2 more Smart Citations
“…There are additional studies that are pertinent to the cognitive disruption hypothesis. Using a Chinese college student sample, Ren et al. (2016) found significant relationships between impulsivity and self-talk frequency.…”
Section: The Cognitive Disruption Hypothesismentioning
confidence: 91%
“…Qualitative (open-ended) research on when, where, and why people talk to themselves supports the four STS subscales/functions (e.g., Morin et al., 2018). Finally, there is good cross-cultural support for the structure and properties of the STS (e.g., Khodayarifard et al., 2014; Ren et al., 2016).…”
Section: The Self-talk Scalementioning
confidence: 99%
See 1 more Smart Citation
“…While questionnaires force participants to endorse pre-existing IS content, sampling methods require reporting specific aspects of inner experiences at random -as a reaction to an external signal, e.g., a beep. Importantly, the studies demonstrate a lot of variability in the amount and the quality of IS reported by participants (Ren et al, 2016). However, this may be due to the participants' reflection abilities rather than to individual variability in the amount of covert speech.…”
Section: Direct and Indirect Measurements Of Ismentioning
confidence: 90%
“…In the field of first-person research, methods of introspection have been used for the investigation of various mental processes, such as imagining a circular object in one's mind (Ziegler & Weger, 2018a), of volitionally controlled perceptual reversals (Wagemann, Edelhäuser, & Weger, 2018), of recollection from memory , and of mind wandering . Furthermore, third-person research uses introspection for the investigation of the content of inner speech (Morin, Duhnych, & Racy, 2018), of the frequency of inner speech (Ren, Wang, & Jarrold, 2016), of the frequency of self-talk (Brinthaupt, Benson, Kang, & More, 2015), of the content of naturally occurring inner experience (e.g. Heavey & 9 Hurlburt, 2008), of the awareness of mind-wandering and mind-blanking (Bastian et al, 2017;Ward & Wegner, 2013), of the possibility of reporting phenomenal experience (Questienne et al, 2018), of experiences during meditation (Przyrembel & Singer, 2018), or of the ex post retrieval of the reasons for making a certain decision (e.g.…”
Section: Empirical Research Using Introspectionmentioning
confidence: 99%